Ženy a muži v časopisech pro ženy: role, perspektivy, výrazově stereotypy - Hoffmanová, Jana (Stylistyka, 2004)
The article deals with the specific style coming into existence in contemporary Czech: the style of popular magazines designed for female readers. An interplay of rol es and perspectives of men and women is one of the characteristic features of the style which is realized in various types of stereotype expressions. Some of them are old and traditional. Others (,,feminine" stereotypes) reflect newly formed relationships between men and women. It is interesting to discover and analyze how men and women name themselves and how they name each other, how they categorize sexes, and to what extent they identify themselves with these - more or less stereotypized - denominations.